Application of research experience into teaching - Ruzaik, Fareena (Geo Book publication, 2021)
Application of research experience into teaching. Why the concept of Green City has become a hot topic?
Application of research experience into teaching on Green city
Keywords: Assessment of public perceptions in desig Colombo Municipal Council ,Green City